Exploring the role of infant temperament in the relationship between self-feeding and parental responsiveness - Alice Di Prete; Jacqueline Blissett; Laura Shapiro; Elsa Addessi; Francesca Bellagamba; Rachel Batchelor; Shefu Islam; Charlotte Webber; Claire Farrow (Appetite, 2026)

Ecology and restoration potential of Ruppia maritima in a managed mosquito impoundment of the Indian River Lagoon, Florida, USA - Deanna F. Webber; Richard E. Mulroy; Patrick H. Monaghan; David C. Heuberger; M. Dennis Hanisak; Rachel A. Brewton (Regional Studies in Marine Science, 2026)

Assessment of a Baited Remote Underwater Video Method to Evaluate American Lobster ( Homarus americanus ) Response to Baits in Nature - L. Grace Walls; Rachel Webber; Laura Brady; Michelle Hodgson; Iain J. McGaw; Russell C. Wyeth (Fisheries Management and Ecology, 2026)
The American Lobster ( Homarus americanus ) is the target of an extensive fishery in the Northwest Atlantic, yet there is no systematic method for evaluating relative performance of baits for the fishery. We used Baited Remote Underwater Video (BRUV) to assess lobster attraction to commercial baits versus natural prey. Significantly higher counts of lobsters in BRUV with commercial baits (herring, mackerel, and rock crab) matched expectations from catches in the fishery. Although location, substrate type, month, and year of deployment also affected lobster counts, the effect of bait type did not depend on any of these potentially confounding factors. Thus, we infer that BRUV can be used to compare lobster responses to different bait types regardless of when or where deployed, providing a useful tool for future initial testing of alternative baits before validation in the fishery.

Productivity, growth, and biogeochemistry of pelagic Sargassum in a changing world - Brian E. Lapointe; Deanna F. Webber; Rachel A. Brewton (Harmful Algae, 2025)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Chemical evolution of shallow playa groundwater in response to post-pluvial isostatic rebound, Honey Lake Basin, California–Nevada, USA - Alan L. Mayo; Rachel M. Henderson; David Tingey; William Webber (Hydrogeology Journal, 2010)